Organic Elemental Composition in Fingernail Plates Varies between Sexes and Changes with Increasing Age in Healthy Humans - Dittmar, Manuela; Dindorf, Willi; Banerjee, Arun (Gerontology (Basel), 2008)
Background: Keratin, an α-helical fibrous protein, is the primary component of human nail plates. No data on age-related changes in healthy subjects are present. Objective: This study investigated whether keratin amount and composition, as indicated by organic elemental composition of fingernails, varies with aging and between sexes. Methods: Nail clippings from 225 healthy individuals (93 males, 132 females), aged 20–90 years, were analyzed for carbon (C), nitrogen (N), and sulfur (S) contents with an automatic elemental analyzer. C/N and N/S ratios were calculated. The C/N ratio is indicative of keratin composition, i.e. the ratio of α-amino acids and protein. The relationship of elemental composition with dietary intake was analyzed by standardized food record. Results: Females have in their nails more sulfur (p < 0.001) and less nitrogen (p = 0.001), and thereby, a lower N/S ratio than males, whereas their carbon content is not different. With aging, the carbon content increases (p < 0.01, both sexes) and the nitrogen content decreases (p = 0.05, females), both leading to an increased C/N ratio (p < 0.001). By contrast, the sulfur content and the N/S ratio do not change with aging (p > 0.05). The carbon content correlates positively with macronutrient intake in females. Nitrogen and sulfur contents are not related with dietary intake. Conclusions: Results suggest that the N/S ratio is indicative of sex differences and the C/N ratio of aging in healthy humans. The increasing carbon content with ongoing age could be explained by loss of inorganic material from the nails, followed by a subsequent increase of organic material. The increasing C/N ratio gives evidence that keratin composition changes towards a higher amount of α-amino acids with aging.